Identifying key predictors of mortality and liver decompensation in hepatocellular carcinoma patients treated with transarterial radioembolization - Mohammad Arabi; Hamdan S. Alghamdi; Abdulaziz A. Almesned; Omar I. Alanazi; Khaled Alzahrani; Meshari A. Alghamdi; Mohammed Bukhaytan; Mohammed F. Alkhalaf; Muath A. Almaimoni; Nawaf A. Alagrafy; Farhan K. Alanazi (The Saudi Journal of Gastroenterology)
Background: This study aimed to identify the predictors of liver decompensation and mortality in patients with HCC treated with trans arterial radioembolization (TARE). Methods: A retrospective analysis of 140 HCC patients who underwent TARE was conducted. Kaplan‐Meier and multivariate Cox regression analyses were performed to identify the key predictors of mortality and liver decompensation, defined as a total bilirubin level greater than 50 μmol/l or an upgrade in the Child‐Pugh class within three months of the first TARE procedure. Results: The cohort comprised 69.3% males with a mean age of 71.3 ± 11.9 years. Most patients (73.6%) had Child-Pugh class A cirrhosis and 34.3% had BCLC stage B disease. Liver decompensation was recorded in 55 patients (39.2%) within three months of the first TARE procedure. A total of 80 patients (57.1%) died during the follow-up period. The median survival was significantly longer in those without liver decompensation (3.2 vs. 0.7 years, P < 0.001). Multivariate analysis revealed that male gender (adjusted odds ratio [aOR] 5.889, P = 0.009), cirrhosis (aOR 6.82, P = 0.047), and baseline international normalized ratio (INR) (aOR 316.664, P = 0.013) were independent predictors of liver decompensation. Cox regression analysis revealed several significant predictors of increased mortality including ascites (HR 2.012, 95% CI, 1.122–3.61; P = 0.019), portal vein invasion (HR 1.695, 95% CI, 1.057–2.718; P = 0.029), and diabetes mellitus (HR 1.823, 95% CI, 1.017–3.265; P = 0.044). Conversely, non-multifocal HCC (HR 0.593, 95% CI, 0.369–0.955; P = 0.031), treatment of the liver lobe other than the right lobe (HR, 0.482; 95% CI 0.236–0.986, P = 0.046), and age ≥60 years (HR 0.288, 95% CI, 0.139–0.597; P = 0.001) were associated with a reduced risk of mortality. Conclusion: This study identified the key predictors of liver decompensation and mortality in patients with HCC undergoing TARE, potentially improving patient selection and management strategies.